Genomic analysis of Leishmania turanica strains from different regions of Central Asia - Novozhilova, Tatiana S; Chistyakov, Daniil S; Akhmadishina, Lyudmila V; Lukashev, Alexander N; Gerasimov, Evgeny S; Yurchenko, Vyacheslav (PLoS neglected tropical diseases, 2023)
The evolution in Leishmania is governed by the opposite forces of clonality and sexual reproduction, with vicariance being an important factor. As such, Leishmania spp. populations may be monospecific or mixed. Leishmania turanica in Central Asia is a good model to compare these two types. In most areas, populations of L. turanica are mixed with L. gerbilli and L. major. Notably, co-infection with L. turanica in great gerbils helps L. major to withstand a break in the transmission cycle. Conversely, the populations of L. turanica in Mongolia are monospecific and geographically isolated. In this work, we compare genomes of several well-characterized strains of L. turanica originated from monospecific and mixed populations in Central Asia in order to shed light on genetic factors, which may drive evolution of these parasites in different settings. Our results illustrate that evolutionary differences between mixed and monospecific populations of L. turanica are not dramatic. On the level of large-scale genomic rearrangements, we confirmed that different genomic loci and different types of rearrangements may differentiate strains originated from mixed and monospecific populations, with genome translocations being the most prominent example. Our data suggests that L. turanica has a significantly higher level of chromosomal copy number variation between the strains compared to its sister species L. major with only one supernumerary chromosome. This suggests that L. turanica (in contrast to L. major) is in the active phase of evolutionary adaptation.
Keywords: zvířata; Mongolsko; Animals; Genomics; Leishmania; Gerbillinae; DNA Copy Number Variations; genomika; variabilita počtu kopií segmentů DNA; Mongolia